Enzyme replacement therapy for murine mucopolysaccharidosis type VII leads to improvements in behavior and auditory function. - O'Connor, L H (1998)
Mucopolysaccharidosis type VII (MPS VII; Sly syndrome) is one of a group of lysosomal storage diseases that share many clinical features, including mental retardation and hearing loss. Lysosomal storage in neurons of the brain and the associated behavioral abnormalities characteristic of a murine model of MPS VII have not been shown to be corrected by either bone marrow transplantation or gene therapy. However, intravenous injections of recombinant beta-glucuronidase initiated at birth reduce the pathological evidence of disease in MPS VII mice. In this study we present evidence that enzyme replacement initiated at birth improved the behavioral performance and reduced hearing loss in MPS VII mice. Enzyme-treated MPS VII mice performed similarly to normal mice and significantly better than mock- treated MPS VII mice in every phase of the Morris Water Maze test. In addition, the auditory function of treated MPS VII mice was dramatically improved, and was indistinguishable from normal mice. These data indicate that some of the learning, memory, and hearing deficits can be prevented in MPS VII mice if enzyme replacement therapy is initiated early in life. These data also provide functional correlates to the biochemical and histopathological improvements observed after enzyme replacement therapy.